Faktor-Faktor Yang Mempengaruhi Kejadian Obesitas Sentral Pada Remaja Di Kota Jambi: Peran Konsumsi Fast Food Dan Riwayat Obesitas Orang Tua - Solihin Sayuti; Ary Irfan; Alpari Nopindra (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2025)
Background: Obesity is a condition in which the body is overweight as measured by several measurements. The accumulation of fat in the subcutaneous tissue of the body, or under the skin, around organs, and sometimes even in the tissue of these organs, is a sign of obesity. In the last five years, the prevalence of adolescent obesity in Indonesia has almost doubled. The purpose of this study was to determine the factors associated with the incidence of central obesity in adolescents in Jambi City. Method: This quantitative descriptive study used a cross-sectional study. In this study, the Solvin formula was used to calculate the number of samples, consisting of 96 adolescents living in the Putri Ayu Health Center work area in 2024. Data collection used a questionnaire. Data processing in the form of univariate and bivariate analysis. The analysis used is chi-square. The study was conducted from April to May 2024. Results: The results of the study showed that there was a relationship between Fast Food Consumption (p = 0.022), Parental Obesity History (p = 0.009) and the incidence of central obesity in adolescents in Jambi City. Conclusion: Factors that can cause obesity in adolescents include unhealthy eating habits, so it is important to maintain a balanced diet, rich in fiber, and frequent consumption of fruits and vegetables.